Monitoramento participativo de sistemas agroflorestais nos assentamentos do município de Iperó - SP - Oliveira, José Eduardo de (2016)
Support the agroecological transition processes in Horto Bela Vista and Ipanema settlements, in Iperó-SP, is an important demand since the entire region is in the buffer zone of the Ipanema National Forest. Recently, farmers from both settlements were awarded projects of implementation of Agroforestry Systems (AFS) in their plots and the monitoring of these areas, through participatory research, is an important strategy in the regional context. This study aimed to follow the agroecological transition of both settlements through participatory monitoring of forest restoration actions with AFS, seeking to evaluate and understand, through the use of sustainability indicators, changes in socio-cultural, economic and ecological aspects arising from these actions. Therefore, workshops were held with farmers and Participatory Rural Appraisal tools were used for raising awareness and building these indicators. Through participatory methodologies, a set of forty indicators were created with attributes related to soil recovery, socioeconomic aspects, socio-cultural aspects, environment and satisfaction. In a second stage, two monitoring were done; one at the end of the dry season and another at the end of the rainy season, between 2015 and 2016. The monitoring was carried out with the use of various techniques and tools that made possible the participation and understanding of farmers throughout the process. The participatory research included the objectives and the reality of the group, contributing to the perception of farmers for the need of constant monitoring to achieve the sustainability of their Agroforestry Systems. The research brought reflection on autonomy of those involved as to the various needs that the AFS have, revealing the main existing obstacles and difficulties among farmers and helped in the process of appropriation of new management techniques in production systems. In addition, it contributed to the discussion of the different dimensions of sustainability and the potential of agroforestry systems to promote agroecological transition and restore ecological processes.